Investigasi Mekanisme Korosi Pada Pipa Pemanas Udara Di Pabrik Gula Pagotan Madiun - Fahrudin Kurniawan; Wawan Trisnadi Putra; Munaji Munaji; Rizal Arifin (TURBO [Tulisan Riset Berbasis Online], 2021)
This study aims to determine the inner surface morphology of pipes and to identify pipe corrosion products using stereo microsocope and X-ray diffraction (XRD) observations. In this study, the sample used was a piece of Blacksteel gas pipe that had been used for 107 days and 570 days with dimensions of 3 cm in length and 4 cm in diameter. The sample was taken from the Air heater Unit of the Pagotan Madiun sugar factory, East Java, Indonesia. Morphology the inside of the tube was observed with a CARL ZEISS Stemi DV4 stereo microscope (32x magnification). Furthermore, the rust material powder on the sample pipe was taken to determine the corrosion product using the XRD X'Pert PRO instrument. The results of observation by using a stereo microscope on the inner surface of air heater pipe that had been used for 107 days and 570 days indicated that the pipe surface experienced corrosion and peeling. From the results of X-ray diffraction (XRD) observations, FeOOH layer were formed from Fe2+ and OH- ions produced from O2 and H2O molecules in the smoke gas from burning bagasse. At the bottom of FeOOH layer, Fe3O4 was formed from the subsequent reaction between FeOOH and Fe2+ ions.Keywords: pipe, air heater, corrosion, smoke gas.